MASALAH KEKERASAN TERHADAP ANAK DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Al Sentot Sudarwanto (Faculty of Law, Universitas Diponegoro, 2011)
Various forms bulying is stiii happening to Indonesian children now, although it has been rules of law and supported by international convention which related with child protection. The extence the rules of law and that convention can't be delayed the existence of child buiying. The form of child bulying which the bumpiest are rapping physical and psychological violence which hamper the growth of child as an adult. Basically the form of bulying child is in contrast with the human right, in this case is children's right. Kata kunci: Kekerasan Terhadap Anak, HAM